Modern Slavery: Analisis Dampak Regulasi Pemerintah Terhadap Ketidak Pemenuhan Hak Pekerja Buruh di Indonesia - Angela Kirana Hartanto; Aulia Khoiriya; Bijak Anugrah; Salsabila Khoirunnisa (International Forum of Researchers and Lecturers, 2024)
In Indonesia, the Job Creation Law has had a major impact on workers, especially in terms of policies that tend to favor companies. The emphasis on labor flexibility and the ease with which companies can restructure can reduce job security, wages, and workers' rights. Inequalities in labor contract negotiations arise as the power differential between companies and workers widens. Thus, modern slavery practices often emerge to make workers feel marginalized. This is due to the lack of legal protection, which is detrimental to their health. Therefore, this study aims to provide an explanation of the effect of government regulation in the form of omnibus law and investment policies on the welfare of workers in terms of wages and working time. To achieve this goal, this research uses a political economy perspective with two derivative theories, namely the theory of oligarchy and neoliberalism. Then, in collecting data, this research will use the big data analytics method that will collect data containing tweets from Indonesians on social media X that contain certain keywords. This method consists of several stages consisting of data cleaning processing, data transformation into tabular form, and data visualization. Besides big data, this research also uses literature review methods to collect data from books, journals, and articles related to this research topic.